2016
DOI: 10.1186/s12879-016-2053-6
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating secondary from primary dengue using IgG to IgM ratio in early dengue: an observational hospital based clinico-serological study from North India

Abstract: BackgroundSecondary dengue causes more severe disease than the primary. Early on, it is important to differentiate the two. We tried to find important clinical and laboratory differences between the two for the purpose of early differentiation.MethodsOne hundred fourteen patients confirmed on reverse transcriptase-polymerase chain reaction (RT PCR) were studied. On day 2 of illness IgM and IgG indices were studied for calculation of IgG/IgM ratio. A one-step immunochromatographic assay was used for classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 24 publications
(25 reference statements)
4
45
2
4
Order By: Relevance
“…The prevalence of secondary dengue infection varied in different studies. Two studies by Sidique O et al 15 and Changal K et al 14 reported the prevalence of secondary dengue infection as 68.4 % and 66.7% respectively, which was higher compared to our study results. However, Kumar et al 16 reported the prevalence of secondary dengue infection as 50%.…”
Section: Discussioncontrasting
confidence: 85%
“…The prevalence of secondary dengue infection varied in different studies. Two studies by Sidique O et al 15 and Changal K et al 14 reported the prevalence of secondary dengue infection as 68.4 % and 66.7% respectively, which was higher compared to our study results. However, Kumar et al 16 reported the prevalence of secondary dengue infection as 50%.…”
Section: Discussioncontrasting
confidence: 85%
“…Delhi, Pune and Hyderabad ( Damodar et al, 2017 ). Various reports from pan India ( Changal et al, 2016 ; Damodar et al, 2017 ; Islam et al, 2016 ; Khan et al, 2014 ; Mishra et al, 2017 ; Muruganandam et al, 2014 and Neeraja et al, 2014 ) and south Asia ( Alera et al, 2016 ; Hapuarachchi et al, 2016 ; Myat et al, 2016 ; Song et al, 2017 and Suleman et al, 2017 ) shows that the co-infections (Infection with more than one serotype), is frequently reported ( Table 4 ). In Dadra & Nagar Haveli the co-infections (infection with more than one serotype) rate is from 7.3% to 17.2% during study period (2014–2016).…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, in the study done by Changal et al in 2016, 11.7% patients had secondary dengue infection. 12 But in the study done by Vikram et al, the secondary infection rate was 25.3%. 13 Regarding other serological parameters, only NS1 Ag in 144(40%) cases.…”
Section: Discussionmentioning
confidence: 92%